Spectroscopic characterization of insulin and small molecule ligand binding to the insulin receptor. Issue 3 (2002) - Schlein Schlein, Morten Morten; Ludvigsen Ludvigsen, Svend Svend; Olsen Olsen, Helle B. Helle B.; Dunn Dunn, Michael F. Michael F.; Kaarsholm Kaarsholm, Niels C. Niels C.
Abstract : We have applied spectroscopic techniques to study two kinds of ligand binding to the insulin receptor. First, a fluorescently labelled insulin analogue is used to characterize the mechanism of reversible 1 :1 complex formation with a fragment of the insulin receptor ectodomain. The receptor induced fluorescence enhancement of the labelled insulin analogue provides the basis for stopped flow kinetic experiments. The kinetic data are consistent with a bimolecular binding event followed by a conformational change. This emphasizes the importance of insulin induced conformational changes in the activation of the insulin receptor. Second, the binding of fluorescein derivatives to the insulin receptor is studied. These small molecule ligands displace insulin from its receptor with micromolar affinity. The binding is verified by transferred NOESY NMR experiments. Their chromophoric properties are used to measure the affinity by UV-vis and fluorescence difference spectroscopies and the resulting Kd values are similar to those observed in the displacement receptor binding assay. However, these experiments and a stoichiometry determination indicate multiple binding sites, of which one overlaps with the insulin binding site. These two examples illustrate how spectroscopy complements biochemical receptor binding assays and provides information on ligand–insulin receptor interactions in the absence of three dimensional structures.